Scrub typhus: risks, diagnostic issues, and management challenges - Prakash, John Antony Jude (Res Rep Trop Med, 2017)
Scrub typhus is an acute febrile illness in the “tsutsugamushi triangle”, transmitted by chiggers that can be treated effectively if detected early. Laboratory testing, including molecular and serological assays, is needed for confirming the diagnosis, especially in the absence of the pathognomonic eschar. In this review, factors that play a role in disease occurrence and clinical clues for diagnosis, in addition to risk factors contributing to disease severity, including mortality, are discussed in detail. Moreover, issues related to diagnostic assays, treatment, and mixed infections are also enumerated and described.